New Putative Antimicrobial Candidates: In silico Design of Fish-Derived Antibacterial Peptide-Motifs - Okella, Hedmon; Georrge, John J.; Ochwo, Sylvester; Ndekezi, Christian; Koffi, Kevin Tindo; Aber, Jacqueline; Ajayi, Clement Olusoji; Fofana, Fatoumata Gnine; Ikiriza, Hilda; Mtewa, Andrew G.; Nkamwesiga, Joseph; Bassogog, Christian Bernard Bakwo; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Antimicrobial resistance remains a great threat to global health. In response to the World Health Organisations’ global call for action, nature has been explored for novel and safe antimicrobial candidates. To date, fish have gained recognition as potential source of safe, broad spectrum and effective antimicrobial therapeutics. The use of computational methods to design antimicrobial candidates of industrial application has however, been lagging behind. To fill the gap and contribute to the current fish-derived antimicrobial peptide repertoire, this study used Support Vector Machines algorithm to fish out fish-antimicrobial peptide-motif candidates encrypted in 127 pep-tides submitted at the antimicrobial peptide database (APD), steered by their physico-chemical characteristics (i.e., positive net charge, hydrophobicity, stability, molecular weight and sequence length). The best two novel antimicrobial peptide-motifs (A15_B, A15_E) with the lowest instability index (-28.25, -22.49 respectively) and highest isoelectric point (pI) index (10.48 for each) were selected for further analysis. Their 3D structures were predicted using I-TASSER and PEP-FOLD servers where ProSA, PROCHECK, and ANOLEA were used to vali-date them. The models predicted by I-TASSER were found to be better than those predicted by PEP-FOLD upon validation. Two I-TASSER models with the lowest c-score of -0.10 and -0.30 for A15_B and A15_E peptide-motifs respectively were selected for docking against known bacterial-antimicrobial target-proteins retrieved from protein databank (PDB). Carbapenam-3-carboxylate synthase (PDB ID; 4oj8) yielded the lowest docking energy (-8.80 and -7.80 Kcal/mol) against motif A15_B andA15_E respectively using AutoDock VINA. Further, in addition to Carbapenam-3-carboxylate synthase, these peptides (A15_B and A15_E) were found to as well bind to mem-brane protein (PDB ID: 1by3) and Carbapenem synthetase (PDB: 1q15) when ClusPro and HPEPDOCK tools were used. The membrane protein yielded docking energy scores (DES) : -290.094, -270.751; coefficient weight (CW): -763.6, 763.3 for A15_B and A15_E) whereas, Carbapenem synthetase (PDB: 1q15) had a DES of -236.802, -262.75 and a CW of -819.7, -829.7 for peptides A15_B and A15_E respectively.Motif A15_B of amino acid posi-tions 2-19 in Pleurocidin exhibited the strongest in silico antimicrobial potentials. This segment could be a good biological candidate of great application in pharmaceutical industries as an antimicrobial drug candidate.